Plasmonic Hepatitis B Biosensor for the Analysis of Clinical Saliva - Riedel, Tomáš; Hageneder, Simone; Surman, František; Pop-Georgievski, Ognen; Noehammer, Christa; Hofner, Manuela; Brynda, Eduard; Rodriguez-Emmenegger, Cesar; Dostálek, Jakub (Analytical chemistry, 2017)
A biosensor for the detection of hepatitis B antibodies in clinical saliva was developed. Compared to conventional analysis of blood serum, it offers the advantage of noninvasive collection of samples. Detection of biomarkers in saliva imposes two major challenges associated with the low analyte concentration and increased surface fouling. The detection of minute amounts of hepatitis B antibodies was performed by plasmonically amplified fluorescence sandwich immunoassay. To have access to specific detection, we prevented the nonspecific adsorption of biomolecules present in saliva by brushes of poly[(N-(2-hydroxypropyl) methacrylamide)-co-(carboxybetaine methacrylamide)] grafted from the gold sensor surface and post modified with hepatitis B surface antigen. Obtained results were validated against the response measured with ELISA at a certified laboratory using serum from the same patients.
Keywords: hepatitida B - antigeny povrchové; Spectrometry, Fluorescence; Humans; zlato; povrchová plasmonová rezonance; imobilizované proteiny; Biosensing Techniques; fluorescenční spektrometrie; Hepatitis B Surface Antigens; Hepatitis B Antibodies; lidé; Biomarkers; biosenzitivní techniky; Saliva; polymery; hepatitida B - protilátky; Polymers; biologické markery; Surface Plasmon Resonance; Immunoassay; sliny; Immobilized Proteins; Gold; imunoanalýza